(untitled) (Dermatology Reports, 2018)
Morphea is a skin disorder characterized by thickening of dermis and subcutaneous tissues and loss of adnexal structures. In the early inflammatory stage of morphea, diagnostic histological findings are absent and this may lead to confusion with other inflammatory dermatoses such as mycosis fungoides (MF). We report two cases of early stage morphea mimicking patchstage of MF. Histopathologic examination of biopsies obtained early in the disease course revealed lymphocytic epidermotropism arranged in small pautrier-like collections as well as linear arrangements in dermal- epidermal junction. Additional biopsies were performed which revealed replacement of subcutaneous fat with closely packed thick collagen bundles under eccrine glands. This report points toward the fact that early stage morphea can simulate MF. Therefore additional evaluation is sometimes required for definite diagnosis.